Analysis of Peripheral Blood IL-6 and Leukocyte Characteristics in 364 COVID-19 Patients of Wuhan - Li, Quan; Xie, Yuyu; Cui, Zhangbo; Tang, Shi; Yuan, Baodong; Huang, Hai; Hu, Yanjie; Wang, Yaling; Zhou, Ming; Shi, Chunwei (Frontiers in Immunology, 2020)
SARS-CoV-2, the pathogen of COVID-19, is spreading around the world. Different individuals infected with COVID-19 have different manifestations. It is urgent to determine the risk factors of disease progress of COVID-19. 364 patients diagnosed with COVID-19, who were admitted to Wuhan Pulmonary Hospital from February 3, 2020 to March 16, 2020, were divided into mild, ordinary, severe and critical groups, according to Chinese novel coronavirus pneumonia diagnosis and treatment plan. Peripheral blood IL-6 and leukocyte characteristics were analyzed, to evaluate the correlation with the severity of COVID-19. The levels of peripheral blood IL-6 were 2.35±0.46pg/ml (mild), 6.48±1.13pg/ml (ordinary), 20.30±5.15pg/ml (severe) and 123.48±44.31pg/ml (critical). The leukocytes were 5.70±0.41×109/L (mild), 6.21±0.14×109/L (ordinary), 6.37±0.26×109/L (severe) and 10.03±1.43×109/L (critical). The lymphocytes were 1.46±0.19×109/L (mild), 1.89±0.14×109/L (ordinary), 1.26±0.07×109/L (severe) and 1.17±0.23×109/L (critical). The neutrophils were 3.63±0.36×109/L (mild), 3.78±0.11×109/L (ordinary), 4.47±0.25×109/L (severe) and 7.92±1.19×109/L (critical). The monocytes were 0.42±0.05×109/L (mild), 0.44±0.01×109/L (ordinary), 0.46±0.02×109/L (severe) and 0.78±0.25×109/L (critical). Conclusively, increase of peripheral blood IL-6 and decrease of lymphocytes can be used as the indicators of severe COVID-19. The increase of neutrophils and monocytes were noticed in critical cases of COVID-19, suggesting that the increase of neutrophils and monocytes should be considered as risk factors of critical cases of COVID-19. Peripheral blood IL-6 and leukocyte characteristics were also analyzed in different age groups. The increase of serum IL-6, decrease of lymphocytes and increase of neutrophils were noticed in patients over 60 years old.